2015
DOI: 10.1002/macp.201500002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Crystallization Rate of Poly(l -lactide) Mediated by a Hydrazide Compound: Nucleating Mechanism Study

Abstract: A low molecular weight hydrazide compound, tetramethylenedicarboxylic di (2-hydroxybenzohydrazide) (TMBH), greatly improves the crystallization rate and crystallinity of poly( Llactide) (PLLA). The nucleating effi ciency of TMBH on the crystallization of PLLA exhibits obvious concentration dependence, which increases fi rst and then decreases slightly with the increase of TMBH loading, reaching a maximum at 0.3 wt%. Time-resolved Fourier transform infrared spectroscopy spectra indicate that the formation of sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 53 publications
0
32
1
Order By: Relevance
“…That is, f EBH as the NA is significantly lower than the amount of EBH incorporated into the PBA matrix. As mentioned above, several multi‐amide organic NAs can self‐assemble into rod‐like crystals via the hydrogen bonding interaction in the PLA matrix . In this work, no visible self‐assembled structure (such as rod‐like crystals) can be found in the polarized optical microscopy image.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…That is, f EBH as the NA is significantly lower than the amount of EBH incorporated into the PBA matrix. As mentioned above, several multi‐amide organic NAs can self‐assemble into rod‐like crystals via the hydrogen bonding interaction in the PLA matrix . In this work, no visible self‐assembled structure (such as rod‐like crystals) can be found in the polarized optical microscopy image.…”
Section: Resultsmentioning
confidence: 65%
“…An ideal NA frequently shows good miscibility with the polymer matrix in the melting state, and presents a higher melting temperature ( T m ) and T c than the polymer matrix, because the polymer/NA composite will transform from the uniform melt into the liquid–solid state before the crystallization of the polymer matrix, which provides heterogeneous nuclei for the subsequent crystal growth of the polymer matrix . It was reported that several low‐molecular‐weight multi‐amide organic derivatives can be partially or completely dissolved in a polylactide (PLA) melt, and further recrystallize and assemble in the subsequent cooling process, leading to the needle, cone and shish‐kebab crystal structures of PLA/NA composites depending on the weight fraction of the NA . These multi‐amide organic derivatives greatly enhance the crystallization rate and T c , and shorten the crystallization time of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…The low‐frequency shifts of v (CO) and v (NH) suggest the existence of weak NH···CO hydrogen bonding interactions between XBU‐ n and PLA chains, as illustrated in Figure B. Similar hydrogen bonding interactions were reported to be existing between PLLA and hydrazide nucleator; which was used to explain the nucleation mechanism of nucleator‐containing of PLLA …”
Section: Resultsmentioning
confidence: 69%
“…Several mechanisms have been proposed to explain the improved nucleation and crystallization of nucleator-containing polymers, for example, epitaxial growth of polymer crystals on nucleator surface, [54] chemical reaction [55] and hydrogen bonding interactions between nucleator and polymer. [46,56,57] FTIR spectroscopy was employed to investigate the possible interactions between PLLA/PDLA matrix and XBU nucleator. Figure 9A shows the FTIR spectra of PLLA, XBU-6, and PLLA/XBU-6 mixtures with different Figure 9B.…”
Section: Proposed Mechanism For Xbu-promoted Sc Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation